Malone Dies and the Beckettian Mimesis of Inexistence - Eric P. Levy (Studies in 20th & 21st Century Literature, 2003)
In the novel, it is not so much that Malone dies as that a mimetic convention concerning the representation of life is terminated or, more precisely, terminally minimalized. Through this reduction of life, Beckettian mimesis is enabled to represent a mode of existence unencumbered by antecedent associations or presuppositions. As the "axioms" (MD 187) and conventions regarding the significance of life are debunked or decomposed, the mimesis of inexistence emerges. But as this state of inexis tence is riddled with paradoxes, an intellectual device is required to facilitate analysis of it. The device in question concerns what metaphysics terms "transcendentals," which determine how we experience what we experience, and thus constrain the boundaries and possibilities of subjectivity. But far from mimicking the method of transcendental phenomenology to uncover the functions by which structure is constituted or filled in, Beckettian mimesis, as exemplified in Malone Dies, seeks instead to represent the process by which structure and order are drained. The hallmark of Beckettian mimesis is the representation of the process by which consciousness is emptied of the content which inexists in it. The deeper implications of this remarkable evacuation can be explored by reference to the doctrine of the kenosis or evacuatio (self-emptying).
Keywords: Malone dies; terminal; terminally; mimetic; mimetic convention; terminally minimalized; Beckettian mimesis; existence; axioms; axiom; decomposed; life; death; inexistence; transcendental; transcendentalism; subjectivity; kenosis; evacuatio; self-emptying; Samuel Beckett